Forsythia Surprise Bouquet Enterprise / Angelin Floren ... [et. al] - Floren, Angelin; Peter, Azlin; Tueng, Tryphosa Faith; Kanyan, Lydia Loney; Ibrahim, Racheal Grace (2022)
Chocolate surprises, bouquets of flowers, balloons and greeting cards are trademarks or key under the Forsythia Surprise Bouquet Enterprise business. The main objective ofthis business is to attract people to buy our surprise delivery gifts to make an individual is happy in a day. The price we give to customers is indeed reasonable with what we offer to customers. In addition, We also want to open a new agenda that opens up opportunities to the public in upgrading our business in the future. As a newly listed company in the market, our company will need to take into consideration all the factors to make sure that it can compete with other companies and satisfy customers' expectations, this is because there are many people involved in this business industry. Moreover, the general manager, administrative manager, marketing manager, operations manager, and finance manager are the other five crucial personnel who help run our company. We all play an important role in this business as well as will ensure this business will succeed smoothly as planned. According to our findings, we are targeting a wide range of customers because our company is placed in a city with a higher probability of attracting customers and convincing them to utilities our services. Additionally, the Forsythia Surprise Bouquet Enterprise's location is quite important because it is close to residential areas and college. With the help ofthe statement offinancial status ofour business, we think we can accomplish our corporate objectives. Finally, we hope that Forsythia Surprise Bouquet Enterprise can grow to be a well-known company in this community and elsewhere and enabling it to occasionally offer better services.